A multiple criteria information system for pedagogical evaluation and professional development of teachers - Filipe, M. N. M.; Ferreira, F. A. F.; Santos, S. P. (Journal of the Operational Research Society, 2015)
Information systems for the evaluation of pedagogical practices aim to improve teaching activity and encourage the pedagogical development of teachers. The implementation of these systems has been interpreted in different ways, depending on each school’s administration board and/or the person responsible for the evaluation process. This ambiguity (and inherent subjectivity) is a barrier to the principles of transparency, equity and fairness in the pedagogical performance evaluation of teachers. From this premise, the main objective of this paper consists in proposing a multiple criteria information system to support the evaluation of pedagogical practices. By combining cognitive mapping and the measuring attractiveness by a categorical based evaluation technique (MACBETH), our framework allows for the conception of a more transparent evaluation system, bringing new insights to the pedagogical appraisal and professional development of teachers. The strengths and weaknesses of our framework are also discussed.